Alexandrium catenella planktonic cell distribution in the Alaskan Arctic (2018-2019) - Fachon, Evangeline; Anderson, Donald (NSF Arctic Data Center, 2021)
During a time of unprecedented ecological change in the Arctic, harmful algal blooms have become an issue of increasing concern. Alexandrium catenella (A. catenella) is a dinoflagellate phytoplankton species which produces toxins known to cause paralytic shellfish poisoning (PSP), inducing sickness in people and marine animals that consume contaminated fish or shellfish. This species is found globally, but the extent and timing of A. catenella blooms in Arctic waters is still being described. This dataset (Alexandrium_AlaskanArctic_WholeCell_2018_2019.csv) includes measurements of Alexandrium catenella cell abundance in water sampled during shipboard surveys in the Northern Bering Sea and Chukchi Sea in late summer of 2018 and 2019 (see methods section for survey details). Water was collected through conductivity, temperature, and depth (CTD) casts as well as from shipboard underway seawater systems, and cell abundances have been paired with concurrent temperature and salinity measurements.